Four Children's Motivations in Memorizing the Qur’an - Yenni Fitria; Ilmi Nadia; Ailsya Regita Ardiningrum; Yulia Sarianti (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2022)
Memorizing the Qur’an is one of the important efforts in the life of a Muslim. To create a generation that has a strong relationship with the Book of Allah, it is important for children to start memorizing the Qur’an from an early age. However, the process of memorizing the Qur’an is not easy, especially for children who are still at their stage of physical and cognitive development. the importance of motivation to start memorizing the Qur’an. This study aims to analyze children's motivation in memorizing the Qur’an. This study used a qualitative method with a case study approach, research data were taken through direct interviews with six informants. All interview and observation data were then analyzed thematically using Miles and Huberman patterns. Overall the results of the analysis show that there are four children's motivations in memorizing the Qur’an at the Rumah Tahfiz. The four motivations are i) encouragement from parents, ii) self-desire, iii) interested in memorizing the Qur'an, and iv) enjoying memorizing the Qur’an. The results of this study can be used as initial data for future researchers in examining different issues related to this problem and various other issues that are relevant to this context.